Why Lyme disease is common in the northern US, but rare in the south: The roles of host choice, host-seeking behavior, and tick density - Ginsberg, Howard S.; Hickling, Graham J.; Burke, Russell L.; Ogden, Nicholas H.; Beati, Lorenza; LeBrun, Roger A.; Arsnoe, Isis M.; Gerhold, Richard; Han, Seungeun; Jackson, Kaetlyn; Maestas, Lauren; Moody, Teresa; et al. (PLOS Biology, 2021)
Lyme disease is common in the northeastern United States, but rare in the southeast, even though the tick vector is found in both regions. This study shows that this is largely because the tick vectors attach abundantly to rodents (which are good hosts for the Lyme bacteria) in the north, and to lizards (which are relatively poor hosts for Lyme bacteria) in the south.